Proportional Guidelines in Ancient Near Eastern Art - Azarpay, Guitty
With three appendices. Appendix A: Wilfred G. Lambert, The Sumero-Babylonian Brick-God Kulla, p. 203-204. Appendix A: W. Heimpel, Gudea's Fated Brick, p. 205-211, 1 fig. Appendix B: Anne Draffkorn Kilmer, The Brick of Birth, p. 211-213.